Atypical work and employment continuity - John T. Addison; Christopher J. Surfield (Institute for the Study of Labor (IZA), 2009)
Atypical employment arrangements such as agency temporary work and contracting have long been criticized as offering more precarious and unstable work than regular employment. Using data from two datasets - the CAEAS and the NLSY79 we determine whether workers who take such jobs rather than regular employment, or the alternative of continued job search, subsequently experience greater or lesser employment continuity. Observed differences between the various working arrangements are starkest when we do not account for unobserved individual heterogeneity. Controlling for the latter, we report that the advantage of regular work over atypical work and atypical work over continued joblessness dissipates.
urn:nbn:de:101:1-20090327340
Keywords: J40; J60; J63; M50; 330; Atypical work; open-ended work; employment continuity; unemployment; inactivity; Ungeschützte Beschäftigung; Arbeitsverhältnis; Arbeitslosigkeit; Erwerbsverlauf; Arbeitsplatzsicherung; USA